Predicting survival following surgical resection of lung cancer using clinical and pathological variables: The development and validation of the LNC-PATH score. (November 2018) - Balata, Haval; Foden, Philip; Edwards, Tim; Chaturvedi, Anshuman; Elshafi, Mohamed; Tempowski, Alexander; Teng, Benjamin; Whittemore, Paul; Blyth, Kevin G.; Kidd, Andrew; Ellames, Deborah; Flint, Louise Ann; et al.
Highlights: The ' LNC-PATH' scoring system is a simple to use and validated prognostic tool. It is calculated using readily accessible variables following lung cancer surgery. It can be used to risk stratify patients according to overall survival. This prognostic tool could have a number of potential clinical applications. Abstract: Introduction: The aim of this study was to develop and validate a simple prognostic scoring system using readily available clinical and pathological variables that could stratify patients according to the risk of death following lung cancer resection. We hypothesized that by using additional pathological variables not accounted for by pathological stage alone coupled with markers of overall fitness a new prognostic tool could be developed. Methods: Multivariable logistic regression analysis of pathological and other clinical variables from patients undergoing surgical resection of non-small cell lung cancer (NSCLC) were used to determine factors independently associated with 2-year overall survival and so derive the scoring system. The model was then validated in an external multi-centre dataset. Results: Using multivariable logistic regression on a large dataset (n = 1, 421) the 'LNC-PATH' (L ymphovascular invasion, N -stage, adjuvantC hemotherapy, P erformance status, A ge, T -stage, H istology) prognostic score was devised and then validated using an external dataset (n = 402). This can be used to risk stratify patients into low, moderate and high-risk groups with a statistically significant difference between the three groups in their survival distributions. 83.8% of patients in the low-risk group survived two years after surgery compared to 55.6% in the moderate-risk group and 26.2% in the high-risk group. The score was shown to perform moderately well with an Area Under the Receiver Operating Characteristic curve (AUROC) value of 0.76 (95% CI: 0.73–0.79) and 0.70 (95% CI: 0.64–0.76) in the derivation and validation cohorts respectively. Discussion: The LNC-PATH score predicts 2-year overall survival after surgery for NSCLC. This may allow the development of risk stratified follow-up protocols in survivorship clinics which could be the subject of future prospective studies.